Discovery and annotation of a novel transposable element family in Gossypium - Hejun Lu (BMC Plant Biology, 2018)
Abstract Background Fluorescence in situ hybridization (FISH) is an efficient cytogenetic technology to study chromosome structure. Transposable element (TE) is an important component in eukaryotic genomes and can provide insights in the structure and evolution of eukaryotic genomes. Results A FISH probe derived from bacterial artificial chromosome (BAC) clone 299N22 generated striking signals on all 26 chromosomes of the cotton diploid A genome (AA, 2x=26) but very few on the diploid D genome (DD, 2x=26). All 26 chromosomes of the A sub genome (At) of tetraploid cotton (AADD, 2n=4x=52) also gave positive signals with this FISH probe, whereas very few signals were observed on the D sub genome (Dt). Sequencing and annotation of BAC clone 299N22, revealed a novel Ty3/gypsy transposon family, which was named as ‘CICR’. This family is a significant contributor to size expansion in the A (sub) genome but not in the D (sub) genome. Further FISH analysis with the LTR of CICR as a probe revealed that CICR is lineage-specific, since massive repeats were found in A and B genomic groups, but not in C–G genomic groups within the Gossypium genus. Molecular evolutionary analysis of CICR suggested that tetraploid cottons evolved after silence of the transposon family 1–1.5 million years ago (Mya). Furthermore, A genomes are more homologous with B genomes, and the C, E, F, and G genomes likely diverged from a common ancestor prior to 3.5–4 Mya, the time when CICR appeared. The genomic variation caused by the insertion of CICR in the A (sub) genome may have played an important role in the speciation of organisms with A genomes. Conclusions The CICR family is highly repetitive in A and B genomes of Gossypium, but not amplified in the C–G genomes. The differential amount of CICR family in At and Dt will aid in partitioning sub genome sequences for chromosome assemblies during tetraploid genome sequencing and will act as a method for assessing the accuracy of tetraploid genomes by looking at the proportion of CICR elements in resulting pseudochromosome sequences. The timeline of the expansion of CICR family provides a new reference for cotton evolutionary analysis, while the impact on gene function caused by the insertion of CICR elements will be a target for further analysis of investigating phenotypic differences between A genome and D genome species.